Be a physiotherapist during Covid-19: a grounded theory study: Covid-19 experience: qualitative study among physiotherapists - Ricci, Emanuela; Menta, Lorena; Simeone, Filomena; Lamberti, Gianfranco; Casati, Vittorio; Ciardi, Gianluca (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Covid-19 pandemic posed a challenge to National Health Systems, both in terms of resources and working setup changes. Introduction of spacing, personal protective equipment, infection prevention measures forced healthcare professionals to change both work contexts and patient-operator and inter-operator relationship dynamics. The present qualitative study aimed to deepen the experience of physiotherapists working at AUSL in Piacenza. Methods: A constructivist grounded theory approach was employed. Initial sampling was achieved through a purposive strategy among physiotherapists working at Department of Rehabilitation Medicine at AUSL in Piacenza. They were firstly contacted by e-mail; for included professional a structured collection of nine audio diaries was employed in the first phase; semi structured interviews were then employed in order to reach data saturation. Data analysis was carried out using the Grounded theory, in order to build a theory based on emerging data. Results: Nine physical therapists accepted to participate; mean (±SD) age of the sample was 46,5 (range 33 to 60 years), and the majority of participants were female (77,8%). Each participant recorded an average of 7.5 audio diaries out of nine; all recruited physiotherapists were then interviewed. Conclusions: Theory that arises from data explains Covid-19 pandemic as a moment of personal and professional growth for physiotherapists, which changed their role by adding communication skills, new knowledge and the need of a multidisciplinary care for their patients, in a continuous process of one’s own role evolution.